Technostress among nurses during electronic medical record implementation: a systematic literature review - AY Yanto; Muzakar Isa; Safari Wahyu Jatmiko (JHeS (Journal of Health Studies), 2026)
The rapid implementation of Electronic Medical Records (EMR) has transformed healthcare documentation but has also introduced new psychological challenges among nurses. This study aims to identify and analyze the relationship between EMR implementation, technostress, and their impacts on nurses’ performance and service quality. Using the PRISMA approach, a systematic literature review was conducted through PubMed and Scopus databases, focusing on studies published between 2020 and 2024. Eight relevant articles met the inclusion criteria, encompassing quantitative, qualitative, and mixed-method designs. The synthesis revealed that EMR systems enhance documentation accuracy and patient safety but simultaneously increase administrative burden, workload, and digital complexity, leading to technostress symptoms such as fatigue, frustration, and decreased focus. These stressors contribute to reduced work efficiency, lower job satisfaction, and potential risks to patient care quality. The review also found that adequate training, organizational support, and user-friendly system design are critical to mitigating technostress and improving adaptation. This study highlights that digital transformation in healthcare requires balanced attention to both technological innovation and human well-being.